ChemInform Abstract: Gold(I)‐Catalyzed Oriented Assembly of Dihydropyridines. Issue 33 (August 2015) - Li, Yufeng; Wu, Zhengguang; Pan, Yi; Huang, Hao; Shi, Jie; Bu, Hongzhong; Ma, Hongfei; Liang, Yingying; Huang, Binbin
Abstract Multisubstituted dihydropyridines (III) are efficiently obtained from methyl propiolate (II) and propargylamines (I) with high regioselectivity.